2021
DOI: 10.1093/eep/dvab003
|View full text |Cite
|
Sign up to set email alerts
|

Controlled human exposures to diesel exhaust: a human epigenome-wide experiment of target bronchial epithelial cells

Abstract: Diesel exhaust (DE) is a major contributor to ambient air pollution around the world. It is a known human carcinogen that targets the respiratory system and increases risk for many diseases, but there is limited research on the effects of DE exposure on the epigenome of human bronchial epithelial cells. Understanding the epigenetic impact of this environmental pollutant can elucidate biological mechanisms involved in the pathogenesis of harmful DE-related health effects. To estimate the causal effect of short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…154 Also, short-term exposure of bronchial epithelial cells to diesel exhaust, a significant contributor to air pollution, alters DNA methylation and could be implicated in pulmonary pathologies. 155 DNA-methyltransferases (Dnmts) play a crucial role in the methylation process. Qin et al showed that the bronchial epithelial Dnmt3b impairs the host defense during Pseudomonas-induced pneumonia, at least in part, by dampening the mucosal responses to flagellin.…”
Section: Genetic and Epigenetic Changes In Bronchial Epitheliummentioning
confidence: 99%
“…154 Also, short-term exposure of bronchial epithelial cells to diesel exhaust, a significant contributor to air pollution, alters DNA methylation and could be implicated in pulmonary pathologies. 155 DNA-methyltransferases (Dnmts) play a crucial role in the methylation process. Qin et al showed that the bronchial epithelial Dnmt3b impairs the host defense during Pseudomonas-induced pneumonia, at least in part, by dampening the mucosal responses to flagellin.…”
Section: Genetic and Epigenetic Changes In Bronchial Epitheliummentioning
confidence: 99%
“…For example, glycosylation of the Fc region of IgG1 can impact antibody function and decreases in IgG1 glycosylation are associated with immune activation and have been observed in asthmatic compared to non-asthmatic children, as well as in murine models of allergic asthma 9698 . Two previous studies have reported DMRs in C5orf63 associated with diesel exhaust inhalation in bronchial epithelial cells and with smoking in peripheral blood samples obtained from a Korean cohort 99, 100 . The C5orf63 DMR observed in this study overlaps with both previously identified C5orf63 DMRs, implying this DMR represents a robust DNAm change across development stages, tissues, and human populations in response to inhaled pollutant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…. Two previous studies have reported DMRs in C5orf63 associated with diesel exhaust inhalation in bronchial epithelial cells and with smoking in peripheral blood samples obtained from a Korean cohort99,100 . The C5orf63 DMR observed in this study overlaps with both previously identified C5orf63 DMRs, implying this DMR represents a robust DNAm change across development stages, tissues, and human populations in response to inhaled pollutant exposure.…”
mentioning
confidence: 90%
“…The epigenome plays a critical role in regulating gene expression in a context-specific manner, such as in specific cell types or in the presence of environmental exposures or disease states. DNA methylation, for example, is responsive to disease promoting exposures in both in vitro cell models 24,[42][43][44] and ex vivo cells from individuals who are healthy and with disease 1,[45][46][47][48] . Yet the DNA methylome has been underexplored and largely limited to the CpGs on commercial arrays.…”
Section: Discussionmentioning
confidence: 99%